TIS – Talking in Symbols. Development of a Tool for Nonverbal Communication after Language Barriers in Pediatric Oncology - Weiler-Wichtl, Liesa J.; Fohn-Erhold, Verena; Schlifelner, Juliana; Fries, Jonathan; Bauer, Erwin K.; Schwarzinger, Agathe; Kienesberger, Anita; Leiss, Ulrike (Klinische Pädiatrie, 2020)
Language barriers have been reported to have a detrimental effect on various outcomes in paediatric care, such as therapy adherence, and may even cause medical treatment errors. To address this issue, we developed a set of 63 cards with which a wide range of specific messages can be conveyed nonverbally in a clinical context. The conceptualization of the tool involved multiple phases. In Study 1, we held a workshop with 11 children and adolescents between 8 and 19 years that had received treatment for oncological conditions to gain an understanding of the specific challenges. In Study 2, we presented a first prototype to 3 children and 14 adults; participants were asked to rate the cards on multiple dimensions. Based on information from the previous trials, we developed a second prototype and asked 10 children and 7 adults to rate the cards on multiple dimensions. In this multidisciplinary approach in addition to our experts of clinical psychology we involved patient advocators and graphic designers in the process to achieve high feasibility and comprehensibility; based on the workshop, expert consensus surveys, data gathered in evaluation, all prototypes and the final card set were developed in close collaboration. Participants had little difficulty interpreting the cards and rated the information content as adequate. Importantly, a majority of participants indicated that they would keep using the tool during their stay at the hospital. Overall, the evaluation implied high acceptance and usability. The final card set is a promising communication tool in clinical paediatric settings with various language barriers. Further research should address how patient outcomes are impacted by using the tool.
Keywords: communication skills; interdisciplinary treatment; practical tools; language barriers; empowerment; psychosocial care